Analisis Metode Dakwah Ali Zaenal Abidin Al-Hamid Di Tawau Provinsi Sabah Malaysia - Nurzizy Binti Sabit (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2021)
ABSTRACTThis study aims to determine the approach, content of lectures and methods of preaching done by the Descendants of the Prophet SAW, Habib Ali Zaenal Abidin Al-Hamid. The additional study also discusses the profile of Habib Ali Zaenal Abidin and the da'wah process carried out by Habib Ali. The research theory uses David Kenneth Berlo's SMCR theory. This writing uses a qualitative descriptive approach. The results showed that Habib Ali Zaenal Abidin Al-Hamid used several rules of practice, such as preaching bil lisan, mujadalah, muidzotil hasanahdan bil hikmah. In terms of conveying the message emphasizes three things: faith, morality, and fiqh with a persuasive approach. This research impacts the effectiveness of da'wah using specific methods to provide better changes to society.Keywords: Dakwah Method, Ali Zaenal Abidin, Tawau, Malaysia